Diagnosing swine flu: the inaccuracy of case definitions during the 2009 pandemic, an attempt at refinement, and the implications for future planning. Issue 3 (19th June 2012) - Mahony, Andrew A.; Cheng, Allen C.; Olsen, Karen L.; Aboltins, Craig A.; Black, James F. P.; Johnson, Paul D. R.; Lindsay Grayson, M.; Torresi, Joseph
<x xml:space="preserve">Abstract</x> Background At the onset of the pandemic H1N1/09 influenza A outbreak in Australia, health authorities devised official clinical case definitions to guide testing and access to antiviral therapy. Objectives To assess the diagnostic accuracy of these case definitions and to attempt to improve on them using a scoring system based on clinical findings at presentation. Patients/Methods This study is a retrospective case–control study across three metropolitan Melbourne hospitals and one associated community‐based clinic during the influenza season, 2009. Patients presenting with influenza‐like illness who were tested for H1N1/09 influenza A were administered a standard questionnaire of symptomatology, comorbidities, and risk factors. Patients with a positive test were compared to those with a negative test. Logistic regression was performed to examine for correlation of clinical features with disease. A scoring system was devised and compared with case definitions used during the pandemic. The main outcome measures were the positive and negative predictive values of our scoring system, based on real‐life data, versus the mandated case definitions'. Results Both the devised scoring system and the case definitions gave similar positive predictive values (38–58% using ascending score groups, against 39–44% using the various case definitions). Negative predictive values were also closely matched (ranging from 94% to 73% in the respective score groups against 83–84% for the case definitions). Conclusions Accurate clinical diagnosis of H1N1/09 influenza A was difficult and not improved significantly by a structured scoring system. Investment in more widespread availability of rapid and sensitive diagnostic tests should be considered in future pandemic planning.